Comparative chloroplast genomes provided insights into the evolution and species identification on the Datureae plants - Su, He; Ding, Xiaoxia; Liao, Baosheng; Zhang, Danchun; Huang, Juan; Bai, Junqi; Xu, Subing; Zhang, Jing; Xu, Wen; Qiu, Xiaohui; Gong, Lu; Huang, Zhihai (Frontiers in Plant Science, 2023)
Generally, chloroplast genomes of angiosperms are always highly conserved but carry a certain number of variation among species. In this study, chloroplast genomes of 13 species from Datureae tribe that are of importance both in ornamental gardening and medicinal usage were studied. In addition, seven chloroplast genomes from Datureae together with two from Solanaceae species retrieved from the National Center for Biotechnology Information (NCBI) were integrated into this study. The chloroplast genomes ranged in size from 154,686 to 155,979 and from 155,497 to 155,919 bp for species of Datura and Brugmansia, respectively. As to Datura and Brugmansia, a total of 128 and 132 genes were identified, in which 83 and 87 protein coding genes were identified, respectively; Furthermore, 37 tRNA genes and 8 rRNA genes were both identified in Datura and Brugmansia. Repeats analysis indicated that the number and type varied among species for Simple sequence repeat (SSR), long repeats, and tandem repeats ranged in number from 53 to 59, 98 to 99, and 22 to 30, respectively. Phylogenetic analysis based on the plastid genomes supported the monophyletic relationship among Datura and Brugmansia and Trompettia, and a refined phylogenic relationships among each individual was resolved. In addition, a species-specific marker was designed based on variation spot that resulted from a comparative analysis of chloroplast genomes and verified as effective maker for identification of D. stramonium and D. stramonium var. inermis. Interestingly, we found that 31 genes were likely to be under positive selection, including genes encoding ATP protein subunits, photosystem protein subunit, ribosome protein subunits, NAD(P)H dehydrogenase complex subunits, and clpP, petB, rbcL, rpoCl, ycf4, and cemA genes. These genes may function as key roles in the adaption to diverse environment during evolution. The diversification of Datureae members was dated back to the late Oligocene periods. These chloroplast genomes are useful genetic resources for taxonomy, phylogeny, and evolution for Datureae.